Moyamoya disease with Sjogren disease and autoimmune thyroiditis presenting with left intracranial hemorrhage after messenger RNA-1273 vaccination: A case report. Issue 6 (11th February 2022) - Lin, Yi-Hsin; Huang, Hsuan; Hwang, Wen-Zern
Abstract: Rationale: The new vaccines are emergently authorized and currently approved for use to protect against the coronavirus disease 2019 (COVID-19) pandemic and serious adverse events are uncommon. Moyamoya disease (MMD) with autoimmune disease is a rare entity and usually presents with intracranial hemorrhage in adults. Patient concerns: We reported a 40-year-old female patient with Sjogren disease and autoimmune thyroiditis, who had received the second dose of Moderna (mRNA-1273) vaccination. Three days later, she presented with left intraventricular and intracerebral hemorrhage as a complication. Diagnosis: After a series of diagnostic workups, left intracranial hemorrhage was associated with MMD. Interventions: Emergent external ventricular drainage and subsequent stereotactic evacuation of hematoma with insertion of intracranial pressure monitoring were performed. Outcomes: Under the care of the neurocritical care team, her physical condition improved gradually. The neurological sequelae was noted by defects of cognitive function, apraxia, agnosia, and impaired executive function. She was discharged after eight weeks with a follow-up in the vascular neurology clinic planning for performing revascularization. Lessons: To the best of our knowledge, no similar case has been reported before, and this is the first case of MMD complicated with intracerebral and intraventricular hemorrhage after mRNA-1273 vaccination. It is noticeable to assess the vaccine safety surveillance and raise the alertness about moyamoya in patients with autoimmune diseases during the COVID-19 pandemic. Further studies for risk evaluation of COVID-19 vaccines in patients with autoimmune diseases might be required in the future.